Civil wars of Congo-Brazzaville (1993-1999)‎ - (:unkn) unknown (My University, 2016)
Following the conference of La Baule in 1990, Congo-Brazzaville opted in 1991, for a national conference. It was an appointment with History, a prelude to democracy.The conference it was assumed, would be the means of the exit from a social and identity crisis, the expression of a political and economic burst.Alas, everyone thought they belonged to the king’s entourage who, as in a court society, would facilitate their personnal and illicit enrichment. This conference, the longest in Africain countries, gave rise to a belligerent impulse and developed an agonal state. It was the start of the extroversion which led political opponents to arm resourceless out-of school youths.This action, tinged with confusion, was to give birth to state and private militia, then to three adventitions wars, driving thousands of people into savannahs and foreigh countries without any hope of retourning to their native country. The art of war became a policy which waged battles.Since the Congolese subsoil represented an obvious economic interest, multinationals financed all three wars. They compelled people to wander, to fear the other, the stranger the journey back home will prove hard for raped women and young people. Hower, those responsible for crimes regainned their legitimacy. The leader’s figurewas thus tarnished even desacralized.We have sought to understand how the institutions crumbled owing to the adventitions wars whether it be the economic sphere or public institutions like school or the church. Finally, our aim was to understand the emergence of a savage order : the order of murder and rape against a background of slanghters with, as target, the death of innoncents.Why has woman, the bearer of life in Africa become the trophy of the powerful and the strong ? If war has a tragic side, why does it arouse so much commitment? War has undoubtedly its grammar, but not its owen logic
Keywords: African Research